Measurement of cold nuclear matter effects for inclusive J/ψ in p+Au collisions at √sNN=200 GeV - Abdallah, Mohamed Samy; Deppner, Ingo Martin; Herrmann, Norbert; Söhngen, Yannick; Weidenkaff, Philipp (Physics letters, 2022)
Measurement by the STAR experiment at RHIC of the cold nuclear matter (CNM) effects experienced by inclusive J/ψ at mid-rapidity in 0-100% p+Au collisions at sNN = 200 GeV is presented. Such effects are quantified utilizing the nuclear modification factor, RpAu, obtained by taking a ratio of J/ψ yield in p+Au collisions to that in p+p collisions scaled by the number of binary nucleon-nucleon collisions. The differential J/ψ yield in both p+p and p+Au collisions is measured through the dimuon decay channel, taking advantage of the trigger capability provided by the Muon Telescope Detector in the RHIC 2015 run. Consequently, the J/ψ RpAu is derived within the transverse momentum (pT) range of 0 to 10 GeV/c. A suppression of approximately 30% is observed for pT<2 GeV/c, while J/ψ RpAu becomes compatible with unity for pT greater than 3 GeV/c, indicating the J/ψ yield is minimally affected by the CNM effects at high pT. Comparison to a similar measurement from 0-20% central Au+Au collisions reveals that the observed strong J/ψ suppression above 3 GeV/c is mostly due to the hot medium effects, providing strong evidence for the formation of the quark-gluon plasma in these collisions. Several model calculations show qualitative agreement with the measured J/ψ RpAu, while their agreement with the J/ψ yields in p+p and p+Au collisions is worse.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 18.05.2022